1995
DOI: 10.1161/01.cir.91.8.2151
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial of the Platelet Integrin Glycoprotein IIb/IIIa Blocker Integrelin in Elective Coronary Intervention

Abstract: This first clinical investigation of Integrelin during routine, elective, low- and high-risk coronary intervention supports the potential efficacy of Integrelin in routine coronary interventions. Pharmacodynamic analyses demonstrate that profound and sustained inhibition of platelet function is achieved, although a higher bolus dose may be required. Definitive assessment of efficacy and safety will need to await a large-scale study powered to achieve statistical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0
3

Year Published

1996
1996
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(99 citation statements)
references
References 24 publications
2
94
0
3
Order By: Relevance
“…Integrelin, a synthetic cyclic heptapeptide with high affinity and marked specificity for platelet GPIIb/IIIa receptors, effectively blocks ADP-induced platelet aggregation (15). A recent clinical study reported that cyclic flow variation developed during coronary angioplasty and coronary stenting in patients with coronary artery disease (16). This study concluded that the use of integrelin during routine, elective, low-and high-risk coronary intervention supports the potential efficacy of integrelin in routine coronary interventions.…”
Section: Clinical Trials Of Anti Platelet Agentsmentioning
confidence: 62%
See 1 more Smart Citation
“…Integrelin, a synthetic cyclic heptapeptide with high affinity and marked specificity for platelet GPIIb/IIIa receptors, effectively blocks ADP-induced platelet aggregation (15). A recent clinical study reported that cyclic flow variation developed during coronary angioplasty and coronary stenting in patients with coronary artery disease (16). This study concluded that the use of integrelin during routine, elective, low-and high-risk coronary intervention supports the potential efficacy of integrelin in routine coronary interventions.…”
Section: Clinical Trials Of Anti Platelet Agentsmentioning
confidence: 62%
“…Pharmacodynamic analysis demonstrated a profound and sustained inhibition of platelet function, although a higher bolus dose may be required. Definitive assessment of efficacy and safety is awaiting current trials to determine statistical significance (16).…”
Section: Clinical Trials Of Anti Platelet Agentsmentioning
confidence: 99%
“…Drug efficacy was based on the literature. [1][2][3][4][5][6] Although the cost of therapy is uncertain, $750 to $1000 is approximately what current GP IIb/IIIa agents cost, and the sensitivity analysis from $500 to $1500 covers the expected range well. Drug efficacy and costs were the 2 primary forms of sensitivity analysis.…”
Section: Limitationsmentioning
confidence: 99%
“…A lthough platelet glycoprotein (GP) IIb/IIIa receptor blockers decrease complications after coronary intervention, [1][2][3][4][5][6] the appropriate selection of patients to receive this form of therapy remains unclear, in part because of concerns about cost. The extreme options are to administer this therapy to all patients or to none.…”
mentioning
confidence: 99%
“…O anticorpo monoclonal contra a GP IIb/IIIa, ou abciximab, tem sido extensivamente estudado em pacientes submetidos a intervenções coroná-rias [5][6][7][8][9][10][11] , sendo o primeiro de uma série de agentes a ser introduzido para o uso clínico. Um número expressivo de outros bloqueadores peptídicos e não peptídicos do receptor plaquetário GP IIb/IIIa também estão sendo avaliados em estudos clínicos de fase II e III [12][13][14][15][16][17][18][19] . Esta atualização tem por finalidade descrever como estes potentes agentes antiplaquetários atuam e discutir as situações clínicas em que há benefí-cio potencial ou demonstrado com o seu uso, baseado nos resultados de estudos clínicos randomizados.…”
unclassified